Ginsenoside Rh2 regulates triple-negative breast cancer proliferation and apoptosis via the IL-6/JAK2/STAT3 pathway - Ding, Rumeng; Kan, Quancheng; Wang, Ting; Xiao, Ran; Song, Yanan; Li, Duolu (Frontiers in Pharmacology, 2025)
IntroductionTriple-negative breast cancer (TNBC) is the most challenging subtype of breast cancer to treat. While previous studies have demonstrated that ginsenoside Rh2 induces apoptosis in TNBC cells, the specific molecular targets and underlying mechanisms remain poorly understood. This study aims to uncover the molecular mechanisms through which ginsenoside Rh2 regulates apoptosis and proliferation in TNBC, offering new insights into its therapeutic potential.MethodsNetwork analysis and transcriptome sequencing were utilized to explore the potential mechanisms of ginsenoside Rh2 in treating TNBC. In vivo imaging and immunohistochemistry were employed to examine the effects of ginsenoside Rh2 in a TNBC mouse model. Functional assays were conducted to assess the impact of ginsenoside Rh2 on TNBC cell behavior. Additionally, ELISA, Western blot, and quantitative real-time PCR were used to further investigate the mechanisms of ginsenoside Rh2-induced apoptosis in TNBC cells.ResultsThrough network analysis, 47 common targets were identified, and Gene Ontology (GO) enrichment analysis suggested that ginsenoside Rh2 may exert therapeutic effects in TNBC by influencing apoptosis, cell proliferation, and protein kinase activity. Both transcriptomic analysis and network analysis revealed the JAK/STAT signaling pathway as a key mechanism. Ginsenoside Rh2 inhibited tumor growth in TNBC mice and reduced the expression of IL- 6, IL-6R, STAT3, Bcl-2, and Bcl-xL in tumor tissues. The ability of ginsenoside Rh2 to inhibit TNBC cell proliferation was further confirmed by attenuating the activation of the IL-6/JAK2/STAT3 apoptosis pathway and reducing the expression of protein kinases AMPK-α1 and PKA-Cα.ConclusionBased on network analysis and experimental validation, our findings demonstrate that ginsenoside Rh2 regulates TNBC proliferation and apoptosis through suppression of the IL-6/JAK2/STAT3 pathway, both in vitro and in vivo. This comprehensive approach represents a significant advancement in understanding the therapeutic potential of ginsenoside Rh2 in treating TNBC.